2009
DOI: 10.1088/0004-637x/704/2/1274
|View full text |Cite|
|
Sign up to set email alerts
|

A Universal Mass Profile for Dwarf Spheroidal Galaxies?

Abstract: We apply the Jeans equation to estimate masses for eight of the brightest dwarf spheroidal (dSph) galaxies. For Fornax, the dSph with the largest kinematic data set, we obtain a model-independent constraint on the maximum-circular velocity, V max = 18 +5 −3 km s −1 . Although we obtain only lowerlimits of V max 10 km s −1 for the remaining dSphs, we find that in all cases the enclosed mass at the projected half-light radius is well constrained and robust to a wide range of halo models and velocity anisotropies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

73
1,030
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(1,106 citation statements)
references
References 89 publications
73
1,030
3
Order By: Relevance
“…The existence of a best-constrained mass despite the parameter degeneracy is broadly in line with empirical results on the robustness of the mass constraint inside the half-light radius from Jeans equation modelling of dwarf galaxies (Walker et al 2009;Wolf et al 2010). The existence of such a characteristic point in the Jeans analysis is further proved by Wolf et al (2010).…”
Section: Towards Understanding the Parameter Degeneracysupporting
confidence: 81%
“…The existence of a best-constrained mass despite the parameter degeneracy is broadly in line with empirical results on the robustness of the mass constraint inside the half-light radius from Jeans equation modelling of dwarf galaxies (Walker et al 2009;Wolf et al 2010). The existence of such a characteristic point in the Jeans analysis is further proved by Wolf et al (2010).…”
Section: Towards Understanding the Parameter Degeneracysupporting
confidence: 81%
“…This physical process mainly depends on the supernovae rate and on the binding energy of the galaxy. Therefore, it is likely to be a critically important factor driving the evolution of low mass galaxies (e.g., Dekel & Silk, 1986;Mac Low & Ferrara, 1999;Ferrara & Tolstoy , 2000;Salvadori et al, 2008) like the Carina dSph, with M tot = 6.1 ± 2.3 × 10 6 M ⊙ within the half radius 241 ± 23kpc (Walker et al, 2009). If the bursts of star formation observed in Carina are part of an ongoing cycle of heating and cooling of an initial gas reservoir (e.g., Stinson et al, 2007;Valcke et al, 2008), there should be a clear evolutionary path in the observed abundances, showing the influence of SNe Ia enrichment at increasing [Fe/H] values.…”
Section: Physical Interpretationmentioning
confidence: 99%
“…The results depend strongly on which dynamical model (Newtonian dynamics or Modified Newtonian Dynamics, MOND, Milgrom 1983) or which dark matter halo scaling relation is assumed (McGaugh et al 2007;Walker et al 2009). We will provide predictions for all these different cases.…”
Section: Introductionmentioning
confidence: 99%